Learning based on library automation in mobile devices: The video production by students of Universidade Federal do Cariri Library Science Undergraduate Degree - Vieira, David Vernon (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
The video production for learning has been evident over the last few years especially when it involves aspects of the application of hardware and software for automation spaces. In Librarianship Undergraduate Degrees the need for practical learning focused on the knowledge of the requirements for library automation demand on teacher to develop an educational content to enable the student to learn through videos in order to increase the knowledge about information technology. Thus, discusses the possibilities of learning through mobile devices in education reporting an experience that took place with students who entered in March, 2015 (2015.1) Bachelor Degree in Library Science from the Universidade Federal do Cariri (Federal University of Cariri) in state of Ceará, Brazil. The literature review includes articles publicated in scientific journals and conference proceedings and books in English, Portuguese and Spanish on the subject. The methodology with quantitative and qualitative approach includes an exploratory study, where the data collection was used online survey to find out the experience of the elaboration of library automation videos by students who studied in that course. The learning experience using mobile devices for recording of technological environments of libraries allowed them to be produced 25 videos that contemplated aspects of library automation having these actively participated in production of the video and its publication on the Internet. Palavras-chave: Information technology. Librarianship. Mobile devices. Mobile learning. Videos Link: http://www.scielo.br/scielo.php?script=sci_arttext&pid=S0103-37862017000300353&lng=pt&nrm=iso&tlng=en